Pendampingan Inovasi Hijau Lestari Alamku Kelurahan Kantalai - Nastia, Nastia; Hartawati, Nanda (Jurnal Pengabdian Kepada Masyarakat Patikala, 2026)
The community assistance program for the innovation “HILAL” (Hijau Lestari Alamku) was initiated in response to low public awareness and participation in environmental management, as well as suboptimal waste management and green space utilization in Kantalai Village. This program aimed to strengthen community capacity in participatory environmental management, promote environmentally friendly practices, and establish a collaborative model between residents and the village government. The implementation methods included socialization sessions, participatory environmental problem mapping, household waste management training, formation of community-based environmental working groups, and practical assistance in planting and maintaining productive and green vegetation. The program involved 45 participants divided into three groups: 15 housewives, 15 youths, and 15 local officials and community leaders. The results indicated an increase in participants’ understanding of waste management and environmental preservation. The housewives’ group successfully implemented household waste segregation and simple composting practices. The youth group initiated routine community clean-up activities and planted 120 tree seedlings in public areas. Meanwhile, local officials and community leaders developed follow-up action plans, including internal regulations and scheduled community service activities. Overall, the program led to initial behavioral changes, the establishment of a village-level environmental management structure, and strengthened collective awareness toward cleanliness and greening efforts. In conclusion, the HILAL innovation assistance program demonstrates that active community engagement is a key determinant of successful community-based environmental management, offering an adaptive and sustainable participatory model at the village level.